2015
DOI: 10.1208/s12248-015-9732-x
|View full text |Cite
|
Sign up to set email alerts
|

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids

Abstract: Abstract. Triple recycling (i.e., enterohepatic, enteric and local recycling) plays a central role in governing the disposition of phenolics such as flavonoids, resulting in low systemic bioavailability but higher gut bioavailability and longer than expected apparent half-life. The present study aims to investigate the coexistence of these recycling schemes using model bioactive flavonoid tilianin and a foursite perfused rat intestinal model in the presence or absence of a lactase phlorizin hydrolase (LPH) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 42 publications
1
32
0
4
Order By: Relevance
“…This result differed from previous reports, which showed that hydrolysis by LPH was a critical first step in the disposition of isoflavonoid glucosides. We used the rat intestinal perfusion model, which has been demonstrated to be suitable for studying the role of LPH (Dai et al, 2015), and found that LPH inhibitor played minimal role in CG absorption and metabolism in the intestine (Fig. 3,D-F ;Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This result differed from previous reports, which showed that hydrolysis by LPH was a critical first step in the disposition of isoflavonoid glucosides. We used the rat intestinal perfusion model, which has been demonstrated to be suitable for studying the role of LPH (Dai et al, 2015), and found that LPH inhibitor played minimal role in CG absorption and metabolism in the intestine (Fig. 3,D-F ;Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Associated with this effort, pharmacokinetic studies have revealed poor bioavailability of these phytochemicals due to extensive metabolism (3). As an example, systematic investigations of genistein intestinal and hepatic disposition have revealed an elaborate integration of intestinal metabolism, and subsequent carrier-mediated apically-directed efflux of metabolites that severely limit genistein systemic bioavailability following oral ingestion (4). …”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies involving quercetin and ileostomists have also been conducted . Several research groups have used mice and rats to study the intestinal metabolism and efflux of other flavonoids . Recycling mechanisms (local, enteric and enterohepatic recycling) have been highlighted for flavonoid metabolites.…”
Section: Introductionmentioning
confidence: 99%